The Titbits of Multi-drug Resistant Organisms Reigning in the Diabetic Foot Ulcers: Regional Epidemiology From a Tertiary Care Hospital of Eastern India - Purba Mukherjee; Kajari Mandal; Atindra Kumar (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2021)
Background and aim: One of the worst complications of diabetes mellitus is diabetic foot infections (DFI). A varied presentation is reported for both the causative bacterial species and their drug resistance patterns. We intended to evaluate the prevalence of drug-resistant strains among aerobic bacterial profile of DFI -as there was no regional data available to implement a rational antibiotic therapy for better management. Materials and methods: This cross-sectional observational study included 102 DFI cases attending this hospital with Wagner grade-1 or above ulcers. Wound swabs were taken from the base of the ulcers after a thorough cleaning. They were inoculated in blood agar, and MacConkey agar and drug sensitivity were performed Kirby Bauer disc diffusion method following the guidelines by the Clinical and Laboratory Standards Institute (CLSI) antimicrobial susceptibility testing standards. Results: Altogether, 135 bacterial isolates were reported with an average of 1.32 bacteria per ulcer with Gram-negative bacilli in 63.7% and Gram-positive cocci in 36.3% cases. However, when individual isolates were considered, Staphylococcus aureus was the commonest species, followed by Klebsiella pneumoniae, Escherichia coli, Acinetobacter baumannii complex, and Pseudomonas aeruginosa. Drug resistance was rampant, with 69.1% multi-drug resistant organisms (MDRO) among them. Methicillin-resistant Staphylococcus aureus (MRSA) was 81.3%, MRCONS 66.7%, and extended-spectrum β-lactamase (ESBL)- producer Gram-negative Bacteria (GNB) 47.3%. Conclusion: In this scenario, Vancomycin and linezolid were the only effective drugs against GPC. Piperacillin-tazobactam and imipenem were effective for GNB in general except ESBL or Metallo-beta-lactamase (MBL) producing Acinetobacter and Pseudomonas species, which showed a dangerous inclination for treatment failure.